THE STRUCTURE OF EXTRACURRICULAR SYSTEM OF EDUCATION IN UKRAINE - Коваленко, Виктория (SWorldJournal, 2020)
The article is devoted to the study of the structural and content of the extracurricular educational system in Ukraine. An overview of the structural and substantive components of extracurricular education in pedagogy.